Diabetic neuropathy: a comprehensive review of prevalence, screening and diagnostic approaches, clinical symptoms, complications and evidence-based management strategies - Elhardalo, Sahr A. O. (International Journal of Research in Medical Sciences, 2026)
Diabetic neuropathy (DN) is a frequent and significant complication of diabetes that has a major impact on patients’ quality of life and contributes to higher rates of illness and mortality. DN impacts approximately 50% of people who have diabetes. It is characterized by distal symmetric polyneuropathy, leading to sensory loss, pain, and challenges with movement. This condition often results in diabetic foot ulcers and the amputation of lower limbs. The onset of diabetic neuropathy is influenced by multiple factors, such as elevated blood sugar levels, dyslipidemia, oxidative stress, mitochondrial issues, and inflammation, all of which can damage peripheral nerves. Despite extensive research, no effective treatments that modify the disease have been identified, and existing methods primarily focus on symptom management. This review explores the complex mechanisms of diabetic neuropathy and highlights recent advancements in its diagnosis and treatment. Recent diagnostic techniques, such as corneal confocal microscopy and biomarker-based tests, have improved the early detection of conditions and the provision of prompt treatment. Modifications in lifestyle and methods that include various healthcare professionals can enhance patient outcomes. Despite significant progress, further research is necessary to develop treatments that can effectively halt or reverse the progression of the disease, which would improve the quality of life for individuals with DN. This review offers a complete summary of the current knowledge and future trends in diabetic nephropathy research and management.